Analisis Kemampuan Peserta Didik Dalam Pemecahan Masalah Spldv Ditinjau Dari Kemampuan Berpikir Kreatif - Rahayu, Putri; Andri Nugroho, Aryo; Zuhri, M. Saifuddin (AB-JME: Al-Bahjah Journal of Mathematics Education, 2025)
Solving mathematical problems is an activity carried out by someone to overcome various difficulties that arise during the learning process. According to Polya, the problem-solving process consists of several stages, including understanding the problem, planning a strategy, implementing the chosen strategy, and reviewing the results obtained. This study to examine students’ ability to solve mathematical problems based on the level of creative thinking skills. The research uses a qualitative descriptive method and involves eighth-grade students of MTs Negeri 1 Demak, who selected based on the results of a creative thinking ability test. Data were collected through written mathematics problem-solving tasks and individual interviews to gain deeper insight into students’ thinking processes. The findings indicate that: (1) students with high creative thinking skills are able to meet all indicators of mathematical problem-solving, starting from understanding the problem to reviewing their answers; (2) students with moderate creative thinking skills are less able to review and evaluate their solutions; and (3) students with low creative thinking skills tend not to recheck their responses and often show a lack of accuracy in solving problems. These results emphasize the importance of developing students’ creative thinking abilities, as creativity significantly influences the quality of problem-solving. The study suggests that consistent practice, exposure to diverse problem types, and guided reflection can contribute to the growth of creative thinking in daily learning activities.